Nanoboomerang-based inverse metasurfaces - A promising path towards ultrathin photonic devices for transmission operation - Zeisberger, Matthias; Schneidewind, Henrik; Huebner, Uwe; Popp, Juergen; Schmidt, Markus A. (APL Photonics, 2017)
Metasurfaces have revolutionized photonics due to their ability to shape phase fronts as requested and to tune beam directionality using nanoscale metallic or dielectric scatterers. Here we reveal inverse metasurfaces showing superior properties compared to their positive counterparts if transmission mode operation is considered. The key advantage of such slot-type metasurfaces is the strong reduction of light in the parallel-polarization state, making the crossed-polarization, being essential for metasurface operation, dominant and highly visible. In the experiment, we show an up to four times improvement in polarization extinction for the individual metasurface element geometry consisting of deep subwavelength nanoboomerangs with feature sizes of the order of 100 nm. As confirmed by simulations, strong plasmonic hybridization yields two spectrally separated plasmonic resonances, ultimately allowing for the desired phase and scattering engineering in transmission. Due to the design flexibility of inverse metasurfaces, a large number of highly integrated ultra-flat photonic elements can be envisioned, examples of which include monolithic lenses for telecommunications and spectroscopy, beam shaper or generator for particle trapping or acceleration or sophisticated polarization control for microscopy.
CRIS-Team Scopus Importer:2023-04-20